Greimas’s Semiotics: Between Structuralism and Phenomenology - Jonkus, Dalius (Problemos, 2019)
Greimas’s semiotics is characterized by an inner duality. This is the inner tension between structuralism and phenomenology. The aim of the paper is to reveal the relationship between structuralism and phenomenology in semiotics. Structuralism and phenomenology have a different understanding of the role of the subject in creating and understanding meanings. Early Greimas understood value systems through the linguistic prism and eliminated the discursive system’s subject itself. Late Greimas’s approach to the subject changed and coincided with the subject of daily experience, who was involved in the selection and creation of meanings. Greimas’s semiotics came closer to phenomenology, but only partially. The concept of bodily and sensory experience in Greimas’s semiotics is constructed from objectivistic positions of science. The body and sensual perception are understood as intermediaries between the inner and outer worlds.
Keywords: Greimas; semiotics; phenomenology; structuralism; subject; sensual perception